1985
DOI: 10.1093/nar/13.20.7341
|View full text |Cite
|
Sign up to set email alerts
|

IndividualXenopushistone genes are replication-independent in oocytes and replication-dependent inXenopusor mouse somatic cells

Abstract: We have assessed the response of many histone H3 mRNAs and an H1C mRNA in Xenopus tissue culture cells after treatment with the DNA synthesis inhibitor hydroxyurea. The amount of the histone mRNAs falls rapidly in response to the inhibitor. This response is prevented by cycloheximide. Cloned Xenopus histone genes were transfected into mouse cells and a cell line was obtained in which the Xenopus genes were actively expressed giving rise to mRNA with correct 5'-termini. The Xenopus genes were correctly regulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
8
0

Year Published

1987
1987
1997
1997

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…The histone H2A and H2B genes in this cluster are transcribed in opposite directions from initiation sites located approximately 235 bp apart. This arrangement of H2A and H2B genes is not unique; it is also found in the genomes of unicellular organisms and other vertebrates (18,21,26,29,38). Histone H2A and H2B genes are often paired and transcribed in opposite directions, even in the genomes of organisms whose histone genes are not generally clustered (26,30).…”
mentioning
confidence: 87%
See 2 more Smart Citations
“…The histone H2A and H2B genes in this cluster are transcribed in opposite directions from initiation sites located approximately 235 bp apart. This arrangement of H2A and H2B genes is not unique; it is also found in the genomes of unicellular organisms and other vertebrates (18,21,26,29,38). Histone H2A and H2B genes are often paired and transcribed in opposite directions, even in the genomes of organisms whose histone genes are not generally clustered (26,30).…”
mentioning
confidence: 87%
“…Transcription ceases upon oocyte maturation and resumes after the midblastula transition, when transcription of zygotic genes begins. Histone gene transcription is DNA replication dependent in most cells of postmidblastula transition embryos and adult frogs (29,35,40). The mechanisms underlying this change in histone gene transcriptional regulation, from constitutive or basal expression in oocytes to S-phase-specific expression in embryos, are not understood.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In Xenopus cells, histone genes are actively transcribed during oogenesis, inactivated when the germinal vesicle breaks down during oocyte maturation, and then reactivated in blastula-stage embryos after fertilization. Because the same histone gene sets are replication independent in oocytes and replication dependent in somatic cells and embryos (37,42), it appears that Xenopus histone gene expression undergoes a transition from constitutive or basal activity during oogenesis to cell cycle-regulated expression later in development by a mechanism that is not well understood.…”
mentioning
confidence: 99%
“…An examination of histone mRNA accumulation has demonstrated that transcripts from genes in both types of clusters are present throughout oogenesis and embryogenesis (32). Analysis of the expression of cloned X. laevis histone genes in cultured X. laevis cells, transfected mouse cells, and frog oocytes has demonstrated that their transcription is replication dependent in somatic cells and replication independent in oocytes (28). The conclusions that have emerged from these and related studies (40) are that no major developmental changes occur in the types of histone genes active during embryogenesis, but that their regulation undergoes a transition from constitutive expression during oogenesis to cell cycle-regulated expression at some point in embryogenesis.…”
mentioning
confidence: 99%